THE PRECLINICAL EFFECT OF NATURAL DRUGS IN COMBINATION WITH CYTOSTATICS UPON THE GROWTH OF THE INITIAL AND DRUG-RESISTANT METASTASIS OF TUMORS - Rakhimov Kairolla Dussenbayevich (Academic Journal of Physical and Chemical Sciences, 2019)
The effect of various combinations of herbal preparations and anti-cancer compounds in rats with drug-resistant models of metastasis of Pliss's lymphosarcoma was studied. Obtained a pronounced antimetastatic effect alhidin combination with vincristine and alhidin with methotrexate in the experiments with the platform, resistant to rubomycin (lack of development of metastases in the inguinal lymph nodes, IL 174%). The combination of the effect of alidina to prospidine (ELE – extended life expectancy -308%) with an increase in immunological (cellular) indicators from them. Metastases did not develop in rats with metastasis of Pliss's lymphosarcoma resistant to lamattina from combinations of alhidin+cyclophosphamide, alhidin+sarcolysine and alhidin + prospidin + cyclophosphamide; ELE – extended life expectancy was 207%. Alhidin on mice with Lewis lung carcinoma as separately, and in combination with platidiam, cyclophosphamide and 5-fluorouracil caused a pronounced anti allergic effect: metastases did not develop 98% of the rats, ELE – extended life expectancy – 248%.